KAJIAN PARAMETRIK KARAKTERISTIK ALIRAN BAHAN BAKAR CNG DALAM REGULATOR TEKANAN DENGAN SIMULASI 3-D (STUDI KASUS : KORELASI PERUBAHAN TEKANAN DALAM REGULATOR DAN LAJU ALIRAN MASSA KELUAR DENGAN ADANYA PERUBAHAN VOLUME DAN PERUBAHAN KONSTANTA PEGAS REGULATOR) - Harmen
Gasoline vehicles can consume CNG fuel instead of gasoline fuel to operate. The vihicles require a set of additional equipment called conversion kit to implement this purpose. Recently, many studies about the peformance of the conversion kit have been performed The studies showed that most of the conversion kit tested in Indonesia required several modifications in order to obtain a high performance. One of the causal factor was do to the pressure regulator could not sufficiently flow the gas in a required amount at the precise time, especially at high speed and full load operations. One of the best way to enhance the performance of the conversion kit is by changing several parameters of the pressure regulator, i.e. the volume and springiness constant of each chamber in the pressure regulator. The project was subjected to a 3-D simulation of the gas flow in the pressure regulator. The simulation was then analysed using a packet of sofware FIRE version 7.0b_v13. The change of pressure value occurred and the performance of the pressure regulator to flow the gas in each chamber was investigated. From the result, it was obtained that there was no a enhancement of the performance for the change of the volume, whether it was an enlargement or reduction of the volume, in fact, there was slightly reduce the performance of the pressure regulator in flowing the CNG fuel. Interestingly, an increase of 17.9% in the first springiness constant, 56. 78% in the second springiness constant, and a reduction of 49.22% in the third springiness constant could enhance the performance of the pressure regulator by 15.3%.